2021
DOI: 10.1093/ecco-jcc/jjab075.032
|View full text |Cite
|
Sign up to set email alerts
|

OP33 Oral ritlecitinib and brepocitinib in patients with Moderate to Severe Active Ulcerative Colitis: Data from the VIBRATO umbrella study

Abstract: Background The efficacy and safety of oral ritlecitinib (JAK3/TEC inhibitor) and brepocitinib (TYK2/JAK1 inhibitor) were assessed in a 32-week Phase 2b induction-maintenance umbrella study (VIBRATO) in participants with moderate to severe active ulcerative colitis who had inadequate or loss of response, or intolerance to corticosteroids, immunosuppressants, or biologic therapies. We report efficacy and safety results from the 8-week induction period of the VIBRATO study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Brepocitinib (PF-06700841), a TYK2 and JAK1 inhibitor, has been clinically promising and well tolerated in the phase I and IIa trials for the treatment of psoriasis [ 84 ], and a phase III trial is currently in progress. Currently, phase II trials are recruiting participants to study brepocitinib as a treatment for CD [ 85 ]. VIBRATO, an umbrella study evaluating the efficacy and safety of brepocitinib and ritlecitinib, which are JAK3 and TEC inhibitors, indicated that both drugs are effective in patients with moderate-to-severe active UC compared to a placebo, as they met all the trial’s endpoints.…”
Section: Biologics and Small Moleculesmentioning
confidence: 99%
“…Brepocitinib (PF-06700841), a TYK2 and JAK1 inhibitor, has been clinically promising and well tolerated in the phase I and IIa trials for the treatment of psoriasis [ 84 ], and a phase III trial is currently in progress. Currently, phase II trials are recruiting participants to study brepocitinib as a treatment for CD [ 85 ]. VIBRATO, an umbrella study evaluating the efficacy and safety of brepocitinib and ritlecitinib, which are JAK3 and TEC inhibitors, indicated that both drugs are effective in patients with moderate-to-severe active UC compared to a placebo, as they met all the trial’s endpoints.…”
Section: Biologics and Small Moleculesmentioning
confidence: 99%
“…Filgotinib 200 mg was efficacious in inducing and maintaining remission compared with placebo in this study. 15 16 Oral brepocitinib and ritlecitinib have completed phase II clinical studies for moderate to severe UC (VIBRATO umbrella study) with primary results suggesting significantly higher proportion of clinical remission and endoscopic improvement (p<0.05) with ritlecitinib 70 mg and 200 mg and brepocitinib 30 mg and 60 mg vs placebo at week 8 17 (table 1).…”
Section: Novel Therapies Jak-stat Inhibitorsmentioning
confidence: 99%
“…Results from a previous phase IIa study demonstrated significant improvements in the Psoriasis Area and Severity Index (PASI) scores in participants with plaque psoriasis treated with brepocitinib compared with placebo (19). Safety results from phase IIa studies of brepocitinib in plaque psoriasis, alopecia areata, and ulcerative colitis demonstrated an acceptable safety and tolerability profile with brepocitinib, with few serious adverse events (SAEs), opportunistic infections, or major adverse cardiovascular events including vascular thrombosis (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%